2014
DOI: 10.1016/j.jvs.2014.08.111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hospital factors on mortality rates after abdominal aortic aneurysm repair

Abstract: Hospitals that complete fewer than five OARs or eight EVARs annually have significantly greater mortality compared with their counterparts. Improved implementation of best practices, more detailed informed consent to include hospital mortality data, and better regional access to health care may improve survival after elective AAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 21 publications
1
20
0
4
Order By: Relevance
“…The influence of volume on surgical outcomes has been seen with some procedures. 22 Volume does affect the rate of CVA, MI, and death after CAS. Low-volume surgeons who perform only one or two cases per year have a 2.52 to 5.78 times increase in risk of complications or death after CAS compared with surgeons who perform three or more cases per year, which is similar to findings from another recent study.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of volume on surgical outcomes has been seen with some procedures. 22 Volume does affect the rate of CVA, MI, and death after CAS. Low-volume surgeons who perform only one or two cases per year have a 2.52 to 5.78 times increase in risk of complications or death after CAS compared with surgeons who perform three or more cases per year, which is similar to findings from another recent study.…”
Section: Discussionmentioning
confidence: 99%
“…The association between hospitals with higher annual procedure volume and improved survival has been demonstrated for most major surgical procedures . Better patient outcomes at higher volume centers have also been reported for percutaneous cardiovascular interventions, such as coronary and valvular procedures, peripheral arterial interventions, and endovascular aortic repair (EVAR) . Building on these findings, several studies have shown that increasing referral of elective EVAR cases to high‐volume centers by a process known as regionalization leads to improved patient outcomes .…”
mentioning
confidence: 94%
“…EVAR proficiency has been attributed to both increased institutional and surgeon volume. 1821 Similarly, good open aneurysm repair outcomes correlate with increasing surgeon and hospital volume. 2225 As inexperienced individual surgeons and institutions get faced with tough open repairs, increasingly they may pass on treating the patient.…”
Section: Discussionmentioning
confidence: 97%